From Compliance to Competitive Edge: Leveraging Technology for Sustainable Hotel Management and Regulatory Advantage in Bali - Putranto, Diyan; Astuti, Marhanani Tri; Halawa, Fransiscus Amonio (Journal of Posthumanism, 2025)
The hospitality industry is increasingly pressured to balance economic success with environmental and social responsibility. This research investigates the unique context of Bali’s 5-star hotel sector, exploring how technological innovation and stakeholder engagement can enhance sustainable practices and translate them into competitive advantages. We propose hypotheses that examine the interplay between advanced technologies, such as Smart Building Systems , the Internet of Things (IoT) and implementation of renewable energy , and their impact on operational efficiency and stakeholder involvement. The study employs a mixed-methods approach, combining quantitative data from 355 respondents, including hotel guests and key stakeholders, with qualitative insights from focus group discussions. Our findings indicate that hotels implementing comprehensive sustainable practices achieve higher market share and brand recognition, supported by significant positive relationships between sustainability, technology adoption, and competitive advantage. This research contributes valuable insights for hoteliers navigating the competitive landscape sustainably while addressing the pressing environmental and social challenges in Bali. By integrating economic prosperity with environmental responsibility, this study positions Bali’s hotels as leaders in sustainable tourism.